The effect of a home exercise program on visio-vestibular function in concussed pediatric patients - Roby, Patricia R.; Podolak, Olivia E.; Grady, Matthew; Arbogast, Kristy B.; Master, Christina L. (Frontiers in Sports and Active Living, 2023)
Background: A visio-vestibular home exercise program (VV-HEP) can provide an equitable and cost-effective method for therapy targeted towards visio-vestibular deficits that are common following concussion. The effects of a VV-HEP on improving concussion symptoms and visio-vestibular function are unclear. Purpose: Determine the effect of VV-HEP on symptoms and visio-vestibular function in concussed pediatric patients. Methods: This study included 527 patients (294 female (55.8%); age=14.4 ± 2.1 years) reporting to a specialty care concussion center within 28 days of injury and for a first follow-up within 60 days of injury. Patients completed the Post-Concussion Symptom Inventory (PCSI) and Visio-Vestibular Examination (VVE). Patients were prescribed the VV-HEP at initial visit, with exercises including saccades, gaze stability, convergence, and balance, and instructed to complete these 1-2 times/day. At follow-up, patients self-reported their VV-HEP progress as 1) has not done, 2) in progress, or 3) completed. Primary outcomes included VV-HEP progress at follow-up, PCSI endorsement and severity, VVE subtests (normal/abnormal), and total VVE score (abnormal=2+ abnormal subtests). Kruskal-Wallis tests and chi-square were used to determine if concussion symptoms or the proportion of abnormal VVE outcomes, respectively, were associated with VV-HEP status. Post-hoc pairwise comparisons with Bonferonni corrections were used to determine concussion symptom (α=0.017 a priori) and VVE (α=0.005 a priori) differences in VV-HEP status. Results: At follow-up, patients who had completed the VV-HEP reported lower symptom endorsement (median=1, IQR=0-3) and lower symptom severity (median=1, IQR=0-4) relative to patients who had not started the VV-HEP (endorsement median=7, IQR=1-13, p<0.0001; severity median=15.5, IQR=2-32.5, p<0.0001) and those in progress (endorsement median=8, IQR=3-14, p<0.0001; severity median=15, IQR=4-30, p<0.0001). A lower proportion of patients who completed the VV-HEP reported with abnormal vestibular-ocular reflex (22.2%), tandem gait (0%), and total VVE score (22.2%) relative to those who had not started or those in progress (P<0.005). Conclusions: Our findings indicate that patients who completed the VV-HEP had lower symptom burden and improved visio-vestibular function relative to those who did not start or were in progress. This suggests that a VV-HEP can effectively reduce visio-vestibular dysfunction following concussion and may serve as a means to minimize inequities in access to care.